Problematika Hukum Pengangkatan Kepala Ohoi - Temorubun, Etmundus Eloresky; Bakarbessy, Andress Deny; Tita, Heillen Martha Yosephine (CAPITAN: Constitutional Law & Administrative Law Review, 2025)
The appointment of the Head of Ohoi in Southeast Maluku Regency is regulated by Southeast Maluku Regency Regional Regulation Number 3 of 2009 concerning Ratshap and Ohoi. At the same time, in accordance with tradition, the appointment of the Head of Ohoi is conducted after the results of the Riin (House of Eyes) deliberation. In practice, the appointment of the Head of Ohoi does not align with Positive Law and related Regional Regulations. The goal of this research is to examine and analyze the legal issues surrounding the appointment of the Head of Ohoi in Southeast Maluku Regency. The research method used is normative juridical, with a Case approach, a Conceptual approach, and a Statute Approach. Legal materials include primary legal materials, secondary legal materials, and tertiary legal materials. The research results indicate that the appointment of the Head of Ohoi in Southeast Maluku Regency is inconsistent with Regional Regulation No. 3 of 2009 concerning Ratshap and Ohoi and The customary law applies. The actions of the Regent of Southeast Maluku are considered procedurally flawed in the appointment because they are contrary to Regional Regulation No. 3 of 2009 concerning Ratshap and Ohoi. Therefore, the appointment process may be canceled.